2015
DOI: 10.1155/2015/604208
|View full text |Cite|
|
Sign up to set email alerts
|

Redox Signaling in Diabetic Nephropathy: Hypertrophy versus Death Choices in Mesangial Cells and Podocytes

Abstract: This review emphasizes the role of oxidative stress in diabetic nephropathy, acting as trigger, modulator, and linker within the complex network of pathologic events. It highlights key molecular pathways and new hypothesis in diabetic nephropathy, related to the interferences of metabolic, oxidative, and inflammatory stresses. Main topics this review is addressing are biomarkers of oxidative stress in diabetic nephropathy, the sources of reactive oxygen species (mitochondria, NADPH-oxidases, hyperglycemia, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 127 publications
(130 reference statements)
2
48
0
Order By: Relevance
“…AGEs are also involved on polarization toward a proinflammatory M1 phenotype and release considerable amounts of proinflammatory factors, as TNFa, which consequentially stimulate production of reactive oxygen species (ROS), leading to subclinical chronic inflammation, glomerular and tubular damage, preceding the albuminuria [21][22][23][24][25]. This increased local production of TNF-a could result in urinary release, which confirms our data.…”
Section: Discussionsupporting
confidence: 86%
“…AGEs are also involved on polarization toward a proinflammatory M1 phenotype and release considerable amounts of proinflammatory factors, as TNFa, which consequentially stimulate production of reactive oxygen species (ROS), leading to subclinical chronic inflammation, glomerular and tubular damage, preceding the albuminuria [21][22][23][24][25]. This increased local production of TNF-a could result in urinary release, which confirms our data.…”
Section: Discussionsupporting
confidence: 86%
“…However, downregulation of nephrin, podocin, and CD2AP by activated AKT in morphine treated mice is a contradiction to the evidence that nephrin, podocin, and CD2AP themselves activate AKT via activation of PI3K to promote survival of podocytes [165]. It is pertinent to note that PI3K/AKT signaling can contribute to hypertrophy of mesangial cells upon activation by TGF- β 1 [166], whereas podocytes may also undergo hypertrophic change in response to high glucose, intraglomerular pressure, and Ang II (Figure 3) [167]. Although ROS can activate PI3K/AKT signaling pathway by inducing AKT phosphorylation [54, 168], they can also be accountable for inactivation of AKT by its diminished phosphorylation [103, 169, 170].…”
Section: Mechanisms Of Ros-mediated Glomerular Renal Injury In Diamentioning
confidence: 99%
“…IV. DISCUSSION Molecular mechanism of diabetic nephropathy includes persistent hyperglycemia that further stimulates the activation of AGEs and results in the appearance of chronic inflammation and oxidative stress [2]. We have demonstrated that MDA level, analyzed by TBARS, as well as blood glucose level were increased on day 56 of diabetes melitus, suggesting a strong correlation between hyperglycemia condition and the oxidative stress formation.…”
Section: Western Blot Analysismentioning
confidence: 69%
“…This complication causes around 44% of all cases of end-stage renal disease and renal failure in the diabetic patients in the United States [1]. Molecular mechanism of diabetic nephropathy includes persistent hyperglycemia which further stimulates the activation of advanced glycation end products (AGEs), chronic inflammation and reactive oxygen species (ROS) [2]. Additionally, NADPH oxidases have been implicated for increased generation of ROS in the diabetic nephropathy [3,4].…”
Section: Introductionmentioning
confidence: 99%